2017
DOI: 10.21307/jofnem-2017-068
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Identification of Longidorus euonymus and Helicotylenchus multicinctus from the Rhizosphere of Grapevine and Banana in Greece

Abstract: Plant-parasitic nematodes such as Longidorus euonymus and Helicotylenchus multicintctus are species widely distributed in central Europe as well as in Mediterranean area. In Greece, both species have been previously reported but no morphometrics or molecular data were available for these species. Nematode surveys in the rhizosphere of grapevines in Athens carried out in 2016 and 2017, yielded a Longidorus species identified as Longidorus euonymus. Similarly, a population of Helicotylenchus multicinctus was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…In relation to H. multicinctus , it is considered the most limiting species of Helicotylenchus in plantain and banana. It was present in the Musa crop production of both Colombia and Brazil, confirming the wide distribution of this plant-parasitic nematode, which also has been previously registered in Puerto Rico, Vietnam, India, Mexico, and Greece ( Ngoc Chau et al, 1997 ; Ravichandra, 2014 ; Lara et al, 2016 ; Tzortzakakis et al, 2017 ). The presence of H. multicinctus in the different production zones, Quindío and Valle del Cauca, suggests a wide spread of this nematode in Colombia, directly related with the dispersion of contaminated seedlings between production zones, but also to environmental conditions that have favored the establishment of this species (altitude, soil type, and nutrient availability for the plant) ( Nath et al, 1998 ; Speijer and Ssango, 1999 ; Araya et al, 2011 ; Godefroid et al, 2017 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In relation to H. multicinctus , it is considered the most limiting species of Helicotylenchus in plantain and banana. It was present in the Musa crop production of both Colombia and Brazil, confirming the wide distribution of this plant-parasitic nematode, which also has been previously registered in Puerto Rico, Vietnam, India, Mexico, and Greece ( Ngoc Chau et al, 1997 ; Ravichandra, 2014 ; Lara et al, 2016 ; Tzortzakakis et al, 2017 ). The presence of H. multicinctus in the different production zones, Quindío and Valle del Cauca, suggests a wide spread of this nematode in Colombia, directly related with the dispersion of contaminated seedlings between production zones, but also to environmental conditions that have favored the establishment of this species (altitude, soil type, and nutrient availability for the plant) ( Nath et al, 1998 ; Speijer and Ssango, 1999 ; Araya et al, 2011 ; Godefroid et al, 2017 ).…”
Section: Discussionsupporting
confidence: 77%
“…The four species identified in this study, H. multicinctus, H. dihystera, H. californicus , and H. erythrinae , have been reported in Musa spp. crops around the world ( Campos et al, 1987 ; Araya and De Waele, 2004 ; Karakas, 2007 ; Dias-Arieira, 2010 ; Ravichandra, 2014 ; Xiao et al, 2014 ; Lara et al, 2016 ; Tzortzakakis et al, 2017 ). However, this is the first report of these species for Musaceae crops in Colombia through integrative taxonomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high intraspecific variability of some diagnostic features and the great diversity in phenotypic plasticity makes species identification based on metric and morphological data of external morphology and internal anatomy difficult and sometimes unreliable. Sequencing of RNA-based markers is a powerful molecular diagnostic approach within this group (Archidona-Yuste et al 2016Palomares-Rius et al 2017;Peraza-Padilla et al 2017;Tzortzakakis et al 2017;Xu et al 2018). Recently, several studies (Archidona-Yuste et al 2016Roshan-Bakhsh et al 2016;Esmaeili et al 2017;Tzortzakakis et al 2017;Xu et al 2017Xu et al , 2018Barsalote et al 2018;Cai et al 2019;Lazarova et al 2019) have shown the usefulness of a pair of molecular markers based on ribosomal RNA (rRNA) (D2-D3 domains of 28S gene and the ITS regions, particularly ITS1) for a fast and precise diagnosis of Longidorus species, even in extreme situations such as sibling and cryptic species.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 14 Longidorus spp. have been reported in Greece, but only nine of these have been molecularly identified: Longidorus closelongatus Stoyanov, 1964 , L. cretensis Tzortzakakis et al, 2001 , L. euonymus Mali and Hooper, 1974 , L. iranicus (= moesicus ) Sturhan and Barooti, 1983 , L. kuiperi Brinkman et al, 1987 , L. orientalis Loof, 1982 , L. pisi (= latocephalus ) Edward et al, 1964 , L. pseudoelongatus Altherr, 1976 , and L. pauli Lamberti et al, 1999 ( He et al, 2005 ; Tzortzakakis et al, 2014 , 2016 , 2017 , 2021 ). For the five remaining species L. africanus Merny, 1966 , L. elongatus ( de Man, 1876 ) Micoletzky, 1922 ,…”
mentioning
confidence: 99%